2018
DOI: 10.1016/j.semcancer.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic drivers of tumourigenesis and cancer metastasis

Abstract: Since the completion of the first human genome sequence and the advent of next generation sequencing technologies, remarkable progress has been made in understanding the genetic basis of cancer. These studies have mainly defined genetic changes as either causal, providing a selective advantage to the cancer cell (a driver mutation) or consequential with no selective advantage (not directly causal, a passenger mutation). A vast unresolved question is how a primary cancer cell becomes metastatic and what are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
229
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(232 citation statements)
references
References 116 publications
2
229
0
1
Order By: Relevance
“…Malignancy is a complex heterogeneous illness introduced through accumulation of different damaging genetic and epigenetic alterations in tumor cells. Notably, disruption of various signaling networks and multiple molecular mechanisms involved in tumor onset and development can lead to extensive deregulation of gene expression profiles in human cancers (Beerenwinkel, Schwarz, Gerstung, & Markowetz, ; Chatterjee et al, ; Du & Che, ). Among identified genetic changes in the cancer etiology, abnormal expression of different gene categories such as tumor suppressors, oncogenes, DNA repair genes, stem cell‐related surface markers and cancer stem cells (CSCs) specific transcriptional factors (TFs), can be noted as leading cause of tumorigenesis (Sadikovic, Al‐Romaih, Squire, & Zielenska, ; Zhao, Li, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Malignancy is a complex heterogeneous illness introduced through accumulation of different damaging genetic and epigenetic alterations in tumor cells. Notably, disruption of various signaling networks and multiple molecular mechanisms involved in tumor onset and development can lead to extensive deregulation of gene expression profiles in human cancers (Beerenwinkel, Schwarz, Gerstung, & Markowetz, ; Chatterjee et al, ; Du & Che, ). Among identified genetic changes in the cancer etiology, abnormal expression of different gene categories such as tumor suppressors, oncogenes, DNA repair genes, stem cell‐related surface markers and cancer stem cells (CSCs) specific transcriptional factors (TFs), can be noted as leading cause of tumorigenesis (Sadikovic, Al‐Romaih, Squire, & Zielenska, ; Zhao, Li, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Carcinogenesis and metastasis are the consequences of the induction of genetic and/or epigenetic alternations. 24,25 A better understanding of the genomic alternations that drive cancer development, especially the metastasis process, is imperative for improving the current therapeutic options and patients' outcome. Recently a large cohort study demonstrated that the metastatic cancers is a highly heterogeneous disease at the genetic, transcriptomic, and microenvironment levels.…”
Section: Discussionmentioning
confidence: 99%
“…This reporter expresses tdTomato protein fused to both a nuclear localization signal (NLS) and nuclear export signal (NES), resulting in shuttling between the cytoplasm and nucleus. Transfection of this reporter into Nup210 knockdown 4T1 cells with or without the nuclear export inhibitor leptomycin B showed no significant differences in nucleocytoplasmic transport of the reporter protein 11 ( Supplementary Fig. 4b).…”
Section: Nup210 Loss Does Not Affect General Nucleocytoplasmic Proteimentioning
confidence: 96%
“…Epigenetic changes such as DNA methylation, histone modification, and chromatin remodeling can also affect gene expression in cancer 10 . Epigenetic silencing of tumor suppressor genes or activation of oncogenes has been implicated in cancer progression 11,12 . These genes can be silenced or activated through widespread alterations in chromatin accessibility due to the gain or loss of heterochromatin regions.…”
Section: Introductionmentioning
confidence: 99%